2013
DOI: 10.1016/j.combustflame.2013.06.012
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and kinetic modelling study of n-butyl formate combustion

Abstract: The oxidation of n-butyl formate, a potential biofuel candidate, is studied using three different experimental approaches. Ignition delay times have been measured for stoichiometric mixtures of fuel and air for pressures of about 20 and 90 bar at temperatures from 846 up to 1205 K in a high-pressure shock tube. A rapid compression machine has been used to determine the low-temperature ignition delay times for stoichiometric mixtures at pressures close to 20 bar over the temperature range from 646 K up to 861 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 30 publications
4
22
1
Order By: Relevance
“…This process is typically facilitated using a small alcohol such as methanol or ethanol, so long chain (C12 and larger) methyl, or ethyl esters respectively result from the conversion. Studies undertaken to date, within RCMs as well as other laboratory devices, have investigated much smaller ester molecules, such as C5 esters, as the low vapor pressures of these fuels and their tendency to stick to the walls of the equipment hampers the use of larger, lower volatility compounds.Vranckx et al[438] measured ignition delay times of stoichiometric mixtures of n-butyl formate. The same study also reported ignition delay measurements from a shock tube and laminar flame speed results.…”
mentioning
confidence: 99%
“…This process is typically facilitated using a small alcohol such as methanol or ethanol, so long chain (C12 and larger) methyl, or ethyl esters respectively result from the conversion. Studies undertaken to date, within RCMs as well as other laboratory devices, have investigated much smaller ester molecules, such as C5 esters, as the low vapor pressures of these fuels and their tendency to stick to the walls of the equipment hampers the use of larger, lower volatility compounds.Vranckx et al[438] measured ignition delay times of stoichiometric mixtures of n-butyl formate. The same study also reported ignition delay measurements from a shock tube and laminar flame speed results.…”
mentioning
confidence: 99%
“…For the lower temperatures, the ignition delay times calculated from the surrogate are shorter and the slope is flatter than the slope from the rapid compression machine (RCM) experiments. However, for ignition delay times greater than 50 ms, heat losses become an increasingly relevant issue also for RCMs with creviced pistons, 19 so the comparability of the RCM results at lower temperatures remains questionable. This example shows that by matching the specified fuel properties, the right balance of functional groups promoting chain branching and chain breaking was found, even if the surrogate composition does not exactly match the functional groups of the real fuel.…”
Section: Experimental and Numerical Setupmentioning
confidence: 99%
“…5,[8][9][10][11][12] By the use of detailed chemical reaction mechanisms, the RIF model inherently accounts for low-and high-temperature auto-ignition, heat release, and pollutant formation. However, despite the focused research on reaction chemistry within the TMFB group and elsewhere, [13][14][15][16][17][18][19][20] chemical reaction mechanisms of novel biofuels are not readily available. New fuel classes containing numerous isomers with partly very different chemical properties have to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The kinetics of small esters such as methyl and ethyl formate has already been studied experimentally in flow reactors, shock tubes, and spherical bombs. 7−9 Similarly, n-butyl formate (BF) oxidation was also investigated by Vranckx et al, 10 who measured ignition delay times and laminar burning velocities of BF/air mixtures under various conditions. They also proposed a detailed kinetic mechanism, mainly based on estimations, to represent their data.…”
Section: Introductionmentioning
confidence: 99%